Characteristics of Polybenzoxazine Aerogels as Thermal Insulation and Flame-Retardant Materials - Shakila Parveen Asrafali; Thirukumaran Periyasamy; Jaewoong Lee (Gels)
Polybenzoxazine-based aerogels are a unique class of materials that combine the desirable properties of aerogels—such as low density, high porosity, and excellent thermal insulation—with the outstanding characteristics of polybenzoxazines—such as high thermal stability, low water absorption, and superior mechanical strength. Polybenzoxazines are a type of thermosetting polymer derived from benzoxazine monomers. Several features of polybenzoxazines can be retained within the aerogels synthesized through them. The excellent thermal resistance of polybenzoxazines, which can withstand temperatures above 200–300 °C, makes their aerogel able to withstand extreme thermal environments. The inherent structure of polybenzoxazines, rich in aromatic rings and nitrogen and oxygen atoms, imparts flame-retardant property. Their highly crosslinked structure provides excellent resistance to solvents, acids, and bases. Above all, through their molecular design flexibility, their physical, mechanical, and thermal properties can be tubed to suit specific applications. In this review, the synthesis of polybenzoxazine aerogels, including various steps such as monomer synthesis, gel formation, solvent exchange and drying, and finally curing are discussed in detail. The application of these aerogels in thermal insulation and flame-retardant materials is given importance. The challenges and future prospects of further enhancing their properties and expanding their utility are also summarized.